Mesenchymal Stem Cells Promote Metastasis of Lung Cancer Cells by Downregulating Systemic Antitumor Immune Response - Marina Gazdic; Bojana Simovic Markovic; Nemanja Jovicic; Maja Misirkic-Marjanovic; Valentin Djonov; Vladimir Jakovljevic; Nebojsa Arsenijevic; Miodrag L. Lukic; Vladislav Volarevic (Hindawi Limited, 2017)
Since majority of systemically administered mesenchymal stem cells (MSCs) become entrapped within the lungs, we used metastatic model of lung cancer, induced by intravenous injection of Lewis lung cancer 1 (LLC1) cells, to investigate the molecular mechanisms involved in MSC-mediated modulation of metastasis. MSCs significantly augmented lung cancer metastasis, attenuate concentrations of proinflammatory cytokines (TNF-α, IL-17), and increase levels of immunosuppressive IL-10, nitric oxide, and kynurenine in sera of LLC1-treated mice. MSCs profoundly reduced infiltration of macrophages, TNF-α-producing dendritic cells (DCs), TNF-α-, and IL-17-producing CD4+ T cells but increased IL-10-producing CD4+ T lymphocytes in the lungs of tumor-bearing animals. The total number of lung-infiltrated, cytotoxic FasL, perforin-expressing, TNF-α-, and IL-17-producing CD8+ T lymphocytes, and NKG2D-expressing natural killer (NK) cells was significantly reduced in LLC1 + MSC-treated mice. Cytotoxicity of NK cells was suppressed by MSC-conditioned medium. This phenomenon was abrogated by the inhibitors of inducible nitric oxide synthase (iNOS) and indoleamine 2,3-dioxygenase (IDO), suggesting the importance of iNOS and IDO for MSC-mediated suppression of antitumor cytotoxicity of NK cells. This study provides the evidence that MSCs promote lung cancer metastasis by suppressing antitumor immune response raising concerns regarding safety of MSC-based therapy in patients who have genetic susceptibility for malignant diseases.